LEVERAGE,UKURAN PERUSAHAAN, LIKUIDITAS DAN KOMISARIS INDEPENDEN TERHADAP PROFITABILITAS PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA (Studi Kasus Pada Perusahaan LQ45 Yang Terdaftar Di BEI Periode 2012 - 2015) - Mayasari Bekti P, 12.05.52.0127; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
The aim of the research is to examine the effect of leverage, Size of Company, Liquidity and  the Independent Comissioner of Profitabilty at LQ45 which listed in the Indonesia Stock Exchange. The population on this research is all LQ45 company in the Indonesia Stock Exchange in 2012 – 2015. The sampling technique used was purposive sampling. The analytical tool was used is Multiple Regression Analysis. The results showed that the leverage and Independent of Comissioner has effect to the profatability of companies. Whereas size of companies and liquidity had no effect on profitability of companies.Key Words  :   Leverage, Size of Company, Liquidity, Independent of Comissioner and Profitability of Company